2020
DOI: 10.5194/tc-14-811-2020
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation of surface observations in a transient marine ice sheet model using an ensemble Kalman filter

Abstract: Abstract. Marine-based sectors of the Antarctic Ice Sheet are increasingly contributing to sea level rise. The basal conditions exert an important control on the ice dynamics and can be propitious to instabilities in the grounding line position. Because the force balance is non-inertial, most ice flow models are now equipped with time-independent inverse methods to constrain the basal conditions from observed surface velocities. However, transient simulations starting from this initial state usually suffer fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 95 publications
2
24
0
Order By: Relevance
“…New techniques have been and will need to be further explored to improve initialization methods using both observed surface elevation and ice velocity changes, allowing for improved understanding of underlying friction laws and rheological conditions of marine-terminating glaciers (Gillet-Chaulet and others, 2016; Gillet-Chaulet, 2020). Observations in regions with large changes can be used to discriminate different parameterizations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…New techniques have been and will need to be further explored to improve initialization methods using both observed surface elevation and ice velocity changes, allowing for improved understanding of underlying friction laws and rheological conditions of marine-terminating glaciers (Gillet-Chaulet and others, 2016; Gillet-Chaulet, 2020). Observations in regions with large changes can be used to discriminate different parameterizations.…”
Section: Discussionmentioning
confidence: 99%
“…Joughin and others (2009), Joughin and others (2019) and Gillet-Chaulet and others (2016) have shown that plastic laws are better suited for fast flowing areas in Pine Island Glacier in the Amundsen Sea Embayment, which in the light of this study makes a strong case for the increased sensitivity of grounding-line retreat and ice-sheet response relative to the commonly used sliding laws. Transient data assimilation (Goldberg and others, 2015; Gillet-Chaulet, 2020) that allow to capture observed rates of change should give better confidence in projections and enable reanalysis to better comprehend processes that drive past changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assimilation methods, on the other hand, capture the present-day geometry, but projections often suffer from unrealistic drifts due to the model responding to inconsistencies in the input datasets. Timedependent data assimilation methods allow for more realistic transients, but to date they have been limited to regional studies or synthetic ice sheet setup (e.g., Goldberg et al, 2015;Gillet-Chaulet, 2020). Other methods include combinations of these techniques, as demonstrated in the initMIP Greenland and Antarctica efforts (Goelzer et al, 2018;.…”
Section: Overview Of the Projection Setup And Their Purposementioning
confidence: 99%
“…To validate the assimilation with independent observations, temperature and salinity profiles from the EN4 data set (EN4.2.1) of the UK Met Office (Good et al, 2013) are used. This collection of in situ data contains about 1000 to 2000 profiles per day at depths between the surface and 5000 m depth.…”
Section: Application Examplementioning
confidence: 99%